Outpatient measurement of arterial stiffness in patients with type 2 diabetes and obesity: 2型糖尿病与肥胖患者在门诊测量的动脉硬化度. (28th July 2016) - Mohammedi, Kamel; Compaoré, Aminata; Potier, Louis; Belhatem, Narimène; Feron, Marilyne; Matallah, Nadia; Travert, Florence; Hansel, Boris; Velho, Gilberto; Roussel, Ronan; Hallab, Magid; Marre, Michel
Abstract: Background: Pulse wave velocity (PWV) is a marker of arterial stiffness. The aim of the present study was to compare PWV in patients with type 2 diabetes mellitus (T2DM) or obesity and healthy subjects in an outpatient setting. Methods: A cross‐sectional study was conducted in patients with obesity without T2DM (n = 37), T2DM without obesity (n = 40), T2DM plus obesity (n = 43), and healthy controls (n = 114). Outpatient measurements of the finger–toe PWV (ftPWV) were made. Results: Mean (± SD) ftPWV was higher in men than in women (10.57 ± 5.02 vs 9.14 ± 3.68 m/s, respectively P = 0.006) and was positively correlated with age ( r 2 = 0.31, P < 0.0001), body mass index ( r 2 = 0.03, P = 0.01), systolic blood pressure (SBP; r 2 = 0.06, P < 0.0001), and right ( r 2 = 0.03, P = 0.01) and left ( r 2 = 0.03, P = 0.01) ankle–brachial index (ABI). Age, SBP and ABI remained significantly correlated with ftPWV in the stepwise regression analysis. Mean ftPWV in controls and in patients with obesity, T2DM, and T2DM plus obesity was 8.32 ± 2.68, 9.50 ± 3.38, 11.29 ± 4.34, and 12.36 ± 6.67 m/s, respectively ( P < 0.0001). These differences remained significant after adjustments for sex, age, SBP, and ABI ( P = 0.008). Although ftPWV was higher in patients with than without macrovascular complications (13.11 ± 6.25 vs 10.40 ± 4.54 m/s, respectively; P = 0.006) in univariate analysis, this was not so in the multivariate‐adjusted model. Conclusions: Outpatient‐measured ftPWV was correlated with age, SBP, and ABI. It was higher in patients with T2DM and obesity compared with healthy controls. The highest ftPWV was observed in patients with both T2DM and obesity. Abstract : Mean (± SD) finger–toe pulse wave velocity (ftPWV) according to type 2 diabetes mellitus (T2DM) or obesity status. Overall P < 0.0001 (ANOVA). * P = 0.03, ** P < 0.0001, *** P < 0.0001.